RANCANGAN WEBSITE LAYANAN PENGADUAN PADA DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KOTA - Suheri; pratiwi, aditia; Batubara, Supina (CV. Hawari, 2022)
Improving public services is a form of government participation in serving the community. Public complaint is a form of participation to play a role in building its environment and as a form of supervision of the performance of government agencies. Reports and aspirations of the community can be used as input to evaluate policies and regulations that have been made or regulations that have been implemented and to find out the problems that exist in the community effectively, quickly and up to date and can directly provide solutions and solutions to exit. The Office of Housing and Settlement Area of Binjai City has the main task of assisting the Governor in implementing decentralization and decentralization authority in the field of Housing, Residential Areas and Land in accordance with the policies stipulated by the laws and regulations. The construction of illegal settlements, because the community must come to the office of the Housing and Settlement Office of Binjai City to report the incident. This becomes ineffective and efficient due to the number of subdistricts that are far from the city center, remote communities become difficult to complain to the Housing Office and Binjai City Residential Area. For this reason, a web-based community complaint service information system is needed to make it easier for people to report all problems. This facility is expected to help connect the community with the Housing Office and Binjai City Residential Area as effectively and efficiently as possible.